2017
DOI: 10.1093/ije/dyw237
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and coronary artery calcification: an investigation using alcohol flushing as an instrumental variable

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“…and Fig. ), which is consistent with the results of a recent study (Yun et al., ). It means that ALDH2 genotype or alcohol flushing can be used as a proxy (an instrumental variable) for the exposure of alcohol consumption.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…and Fig. ), which is consistent with the results of a recent study (Yun et al., ). It means that ALDH2 genotype or alcohol flushing can be used as a proxy (an instrumental variable) for the exposure of alcohol consumption.…”
Section: Discussionsupporting
confidence: 93%
“…For example, several studies evaluated the value of the alcohol flushing questionnaire to identify individuals susceptible to various alcohol‐related disorders (Gonzalez et al., ; Yokoyama et al., ). To date, there have been several Korean studies using alcohol flushing questionnaires to elucidate the association between alcohol drinking and some diseases (Jung et al., ; Yun et al., ). However, alcohol flushing questionnaires used in these studies were not validated.…”
mentioning
confidence: 99%
“…A recent study in South Korea showed that genetic polymorphisms in ALDH2 are correlated with stroke in men only,62 raising the possibility that the observed association is mainly attributable to the strong correlation mediated by alcohol intake, especially in men. Further, very recently, it has been suggested that alcohol flushing can be used as an instrumental variable to evaluate the health impact of alcohol consumption, since alcohol flushing is closely related to ALDH2 deficiency 63. Using a phenotypic proxy of a genotype allows researchers to achieve MR-inspired causal inference even genetic data are absent 64…”
Section: Mendelian Randomization Analysis Based On Aldh2 Polymorphismsmentioning
confidence: 99%
“…Compared with cardiac protection, the role of ALDH2 in atherosclerosis remains poorly defined. A recent epidemiological study in East Asian populations using alcohol flushing status as an instrumental variable demonstrated that increased alcohol consumption was positively associated with an increased risk of subclinical coronary atherosclerosis, suggesting that ALDH2 might be involved in the pathogenesis of atherosclerosis (26). A previous study using APOE-KO mice infected with an ALDH2-expressing lentivirus or ALDH2 RNAi lentivirus found that ALDH2 had a protective role in atherosclerosis through attenuating the inflammation in endothelial cells (17).…”
Section: Ampk Plays An Important Role In Regulating Endocytosis and Amentioning
confidence: 99%